Cryoelectron microscopy with elemental sensitivity - Ochner, Hannah; Bharat, Tanmay A.M. (Structure (London), 2025)
In a recent issue of Nature Methods, Pfeil-Gardiner et al. (2024)1 combine electron energy-loss spectroscopy and single-particle cryoelectron microscopy to allow the spatially resolved imaging of the elemental composition of macromolecules. In a recent issue of Nature Methods, Pfeil-Gardiner et al. (2024) combine electron energy-loss spectroscopy and single-particle cryoelectron microscopy to allow the spatially resolved imaging of the elemental composition of macromolecules.